Perlindungan Hukum Terhadap Kebocoran Data Pribadi Pada Platform Media Sosial - Tomasoa, Gelsy Olivia (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Personal data as a form of self-representation of a human being must be used based on the owner's permission if it is not classified as a violation especially if the data was obtained as a result of an application data leak which can then be accessed on social media platforms which causes the owner's life to be threatened.Purposes of the Research: To review and analyze the leakage of personal data on social media platforms can be classified as a form of violation of human rights and its legal protection.  Methods of the Research: This research is a normative legal research with the research approach method used is a statutory approach and a conceptual approach.Results of the Research:  Leakage of personal data is included in human rights violations because it causes material and even non-material losses in the form of a violation of a person's right to life to be free from any threat and disturbance from others. The legal protection provided is in the form of administrative sanctions, namely the temporary suspension of personal data processing activities, which means that data accessing activities on the PeduliLindungi application so that it is not allowed to carry out the process of changing or uploading personal information of a person or person within a certain time frame with the aim.